2003
DOI: 10.1136/gut.52.9.1271
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of meal induced gastric accommodation by a satiety drinking test in health and in severe functional dyspepsia

Abstract: Aims: Impaired gastric accommodation is a major pathophysiological mechanism in functional dyspepsia. The aim of the present work was to assess a satiety drinking test in the evaluation of accommodation in health and dyspepsia. Methods: Twenty five controls and 37 severely dyspeptic patients seen at a tertiary care centre completed a dyspepsia questionnaire, and gastric emptying and gastric barostat studies. The amount of liquid meal ingested at maximum satiety during a slow satiety drinking test was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
261
4
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(292 citation statements)
references
References 34 publications
19
261
4
8
Order By: Relevance
“…In this test, a standardized liquid nutrient drink, such as Ensure (1 kcal/ml, 11% fat, 73% carbohydrate, and 16% protein), is ingested at a standard rate of 30 ml per min, and the maximum tolerated volume, used as a measure of satiation by the symptoms of nausea, bloating, and pain, can also be measured 30 min after the meal (21). Tack et al (121) suggested that a high-caloric, slowly administered drinking test compared favorably with the barostat in predicting impaired gastric accommodation. However, in healthy controls and in a sample of people in the community with functional dyspepsia, the maximum tolerated volume only explained 13 and 3% of variations in fasting and postprandial volumes, respectively, measured by SPECT (56).…”
Section: Satiation or Nutrient Drink Testmentioning
confidence: 99%
“…In this test, a standardized liquid nutrient drink, such as Ensure (1 kcal/ml, 11% fat, 73% carbohydrate, and 16% protein), is ingested at a standard rate of 30 ml per min, and the maximum tolerated volume, used as a measure of satiation by the symptoms of nausea, bloating, and pain, can also be measured 30 min after the meal (21). Tack et al (121) suggested that a high-caloric, slowly administered drinking test compared favorably with the barostat in predicting impaired gastric accommodation. However, in healthy controls and in a sample of people in the community with functional dyspepsia, the maximum tolerated volume only explained 13 and 3% of variations in fasting and postprandial volumes, respectively, measured by SPECT (56).…”
Section: Satiation or Nutrient Drink Testmentioning
confidence: 99%
“…Cuomo et al [11] reported that in females with functional dyspepsia, the correlation between maximal tolerated drink test volume and the fractional rate of gastric emptying was 0.48 (P = 0.0003, Figure 4). Tack et al [8] also reported a weak but significant correlation between maximal tolerated volume for the nutrient drink test and the half time of gastric emptying for a solid meal when pooled controls and patients with functional dyspepsia were studied (r = -0.40, P = 0.001). The correlation was not statistically significant when only evaluating patients with functional dyspepsia.…”
Section: Drink Tests and Gastric Emptyingmentioning
confidence: 99%
“…Logically, it would seem that incrementally distending the stomach by drinking could achieve a result similar to incrementally distending the stomach using a balloon on the end of a catheter. Indeed, Tack et al [8] have reported a good correlation between barostat-measured accommodation and total calories consumed during a nutrient drink test administered at 15 mL/min. For both patients with functional dyspepsia and controls, the correlation was 0.76 (P < 0.001) and the nutrient drink test was calculated to have a sensitivity of 92% and a specificity of 86% in predicting impaired gastric accommodation.…”
Section: Drink Tests and Accommodationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a simple and noninvasive method compared to the "gold standard" electronic barostat (17). Reduction in maximum intake of a liquid diet indicates impairment of gastric accommodation.…”
Section: Obesity Biology and Integrated Physiologymentioning
confidence: 99%